Teachers’ experiences and perceptions on the quality of teaching and learning in private early learning centres (PELCS) in South Africa - Phajane, Masello Hellen (Penerbit Universiti Kebangsaan Malaysia, 2019)
Empirical research has confirmed the importance of quality of teaching and learning in Private Early Learning Centres (PELCs) to subordinates in improving the quality of teaching and learning. This study investigated the nature of quality of teaching and learning in Private Early Learning Centres (PELCs) provided at previously marginalised Private Early Learning Centres (PELCs) of the Gauteng Province in South Africa. To meet this objective qualitative research design was used. The subjects of the study were all purposefully selected teachers, Head of Department and School Manage Team (SMT). Data was collected through observations and semi structured interviews (individual and focus group). The total number of 14 purposefully selected participants took part in the research. Participants were selected according to the socio-economic status of their school. A theoretical framework, based on a model of quality development by Woodhead, informed the study. The findings showed that the quality of teaching and learning in PELCs compromised the quality of teaching. Teachers were also very vocal about the absence of support they get with regard to classroom practices from the School Management Team (SMT). The Head of Department also mentioned lack of knowledge of quality of teaching and learning in PELCs practices, work overload and limited time as challenges that inhibit them to provide the needed support.